INCREASING THE FIRE RESISTANCE OF POLYMER BUILDING MATERIALS BASED ON TECHNOGENIC WASTE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Today, comprehensive measures are being implemented around the world and certain results are being achieved in the field of further deepening economic reforms in the building materials industry and the rapid development of the network, increasing the production of new modern building materials, structures and products, and expanding their range. Expanding the range of manufactured building materials, increasing the share of production of modern, convenient, and high-quality products based on a localization program, reducing imports, as well as the further development of the industry remain pressing issues of today.The studies present methods for increasing the fire resistance of polymer building materials obtained based on fly ash from the furnaces of the Shirin Thermal Power Plant and JSC Uzmetkombinat, waste phosphogypsum generated at JSC Maxam-Ammafos, physical, mechanical, and thermodynamic properties, and also studied optimal proportions for obtaining composites of fire-resistant polymer building materials.To conduct an experimental study, particles of technogenic industrial waste of the most optimal size, types of filler, and necessary components were selected. Studies of the elemental composition of industrial technogenic waste and X-ray diffraction analysis have shown that they consist mainly of silicon dioxide, which consists of more than 80% of the amorphous phase.Based on the analysis of the X-ray phase structure, it was determined that the introduction of additives into the fly ash fillers of the Shirin Thermal Power Plant and Uzmetkombinat JSC, as well as phosphogypsum waste from Maxam-Ammofos JSC, leads to an increase in the thermal stability of polymer materials. The main reason for this is explained by the fact that the composition of fly ash and phosphogypsum waste introduced into the polymer composite contains metal oxides, silicon oxide, and phosphorus compounds, which are resistant to temperatures and have fire-retardant properties.The fire resistance properties of the proposed polymer-containing building materials modified with fire-resistant compositions of the PPA, PPK and PPM brands, consisting of polymer binders, fire-retardant additives and fillers, were studied based on experimental tests, while the oxygen index was increased from 18.5 to 33.0%, while the weight loss during thermal oxidation was reduced from 97.5 to 73–75.5%, and the flammability level according to state standard 28157 was changed from PV-2 to PV-0. ;